CHARACTERIZATION AND POLYPHASIC IDENTIFICATION OF NOVEL RHIZOBACTERIA STRAIN ISOLATED FROM SAND DUNES ECOSYSTEM - Ketut Arte Widane; Annisaa Widyasari; Endah Retnaningrum (BIOTROPIA, 2022)
The coastal sand dune ecosystem at the Parangtritis Coast of Yogyakarta, Indonesia has unique characteristics such as low moisture sandy soil, high salinity and low nutrient content. Fimbristylis cymosa is one of the plant species having the capability to survive in that unique ecosystem. In this study, rhizobacteria isolated from the rhizosphere of F. cymosa were isolated to be further analyzed on their phosphate solubilizing and antagonistic properties against Fusarium oxysporum which cause the Wilt disease. The isolates of Phosphate Solubilizing Rhizobacteria (PSR) having the most potential capabilities were then polyphasically identified based on phenotypic and genotypic characters followed by 16S rDNA sequencing. The results showed that four PSR isolates (I8, I11, I12 and I24) have high phosphate dissolution indices. The highest indices were observed in isolates I11 (3.08) and I12 (3.44), respectively. Analysis of the dual plate experiments for PSR I11 and PSR I12 isolates against the growth of F. oxysporum also showed quite high inhibitory activities, i.e., isolate PSR I11 was 42.40%, while isolate PSR I12 was 42.08%. The two isolates were polyphasically identified as Burkholderia dolosa. This study clearly showed that PSR I11 and PSR I12 isolates are very potential and prospective to be used as marginal land inoculants and as providers of phosphorus. This study also showed that the isolates are useful as biocontrol agents against F. oxysporum in plants.